Lexical Problems in Indonesian-Arabic Translation at the Undergraduate Arabic Department - Azwir Azwir (EL-MAQALAH : Journal of Arabic Language Teaching and Linguistics, 2023)
This paper investigates the issue of lexical errors encountered by Arabic Language Education students at UIN Ar-Raniry in translation. This research takes the form of a content analysis, which investigates the outcomes of the translation jobs they perform in terms of lexical mistakes. According to the research findings, pupils had significant challenges when it came to employing vocabulary, which was separated into verb vocabulary and noun vocabulary. There is still an error in the selection of words or their equivalents in the target language. Furthermore, mastery of the word structure is still quite limited, and the feature of short length in Arabic is still overlooked.